PENGARUH INDEPENDENSI AUDITOR, PENGALAMAN KERJA AUDITOR, KOMPLEKSITAS AUDIT, TIME BUDGETPRESSURE, DAN DUE PROFESSIONAL CARE TERHADAP KUALITAS AUDIT (STUDI KASUS PADA KANTOR AKUNTAN PUBLIK DI PALEMBANG) - Samuel Dio Gyer; Harun Delamat; Ubaidillah Ubaidillah (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2018)
This research aimed to analyze and provide empirical evidence of the influence of auditor’s independency, auditor’s work experience, audit complexity, time budget pressure, and due professional care toward audit quality. The population was all of auditor who works at Accounting Public Firm in Palembang. The sample used in this research was saturated sampling which all of auditor agree to be respoden were 37 auditor. The sample was taken using the method of purposive sampling, and those meeting the selection criteria were also taken. The statistic method used was multiplied regresion analysis used SPSS 20 with hypothesis testing of statistic t and F test.The results of research show that : auditor’s independency, auditor’s work experience, audit complexity and due professional carehave positive and significant influence to audit quality partially. Variable time budget pressure has no and significant influence to audit quality. Variable auditor’s work experience was a dominant for influencing audit quality. Variable auditor’s independency, auditor’s work experience, audit complexity, time budget pressure, and due professional care have positive and significant effect on audit quality simultaneously amounted to 52.5%.